FINANCIAL STABILITY AS AN INDICATOR OF THE EFFICIENCY OF USING THE COMPANY’S FINANCIAL RESOURCES - NIKOLCHUK, Yuliia; NEBZYTSKYI, Bohdan; SAVCHUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The relevance of the chosen topic of scientific research is determined by the fact that today the main criterion that determines the quality of the management of the company’s financial resources is its financial stability. This component of the general financial condition of the enterprise reflects the ability of the business entity to fulfill its obligations to creditors and founders. Financial stability reflects the current state of the company’s accounts, which guarantee its constant solvency. Such an entity is considered financially stable management, which, in the event of unfavorable changes in the conditions of the external and internal environment, is able to return to a state of equilibrium with the help of its own resources. Analysis theoretical foundations for operating financial stability indicators provides an opportunity find out what state the company’s activity is in at the moment. The system of indicators of financial stability makes it possible to implement measures to improve the financial condition of the enterprise, provided that the indicators have a dispositive value. Activities regarding the improvement of the state of the enterprise are possible due to the presence of managers who are capable make and implement optimal management decisions. The article defines the place of financial stability in the overall stability of the enterprise. The directions in which the concept of "financial stability of the enterprise" is interpreted are defined. The essence of the financial stability of the enterprise in the "narrow" and "broad" sense is considered. Various scientific approaches to the interpretation of the concept of "financial stability of the enterprise" have been studied, with the most complete and accurate ones being singled out. The content of the concept of financial stability of the enterprise is summarized. The characteristic features inherent in the financial stability of the enterprise are defined. The indicators that are calculated during the analysis of the financial stability of the enterprise are characterized. Further research will be aimed at researching the methodology of conducting an analysis of the financial stability of the enterprise.